(untitled) (Research, Society and Development, 2022)
Introduction: Sex and gender are fundamental, but completely different. Biological sexual characteristics, it can be said that they are always the same and do not change according to time, culture and much less society. Transvestites and transsexuals have always been at the forefront of prejudice and discrimination against the LGBT population in Brazil. This is because this population has a different gender identity from that imposed by heteronormative standards and anything that deviates from this norm is viewed with estrangement. Objective: To analyze the access of the transvestite and transsexual population to health services in the state of Rio de Janeiro during the COVID-19 pandemic. Methodology: A cross-sectional study that was carried out with transvestites and transsexuals from municipalities in the state of Rio de Janeiro during the COVID-19 pandemic from October 2021 to February 2022. Results: It was possible to observe that of the twenty-nine responses, the profile formed was the majority with 20-24 years old, transgender, single, of black or brown race/color and with a complete high school course.. In addition, most reports indicate that there was more than one barrier present in their access to health. Conclusion: The socioeconomic profiles found are in accordance with the few indicators that exist in Brazil, it was possible to observe and conclude that many access barriers were found for this population, including prejudice and the lack of preparation of professionals for their care.